Just breathe : comparing visual and musical breathing cues in resonance frequency breathing - Rastin, Molly (2019)
Heart rate variability (HRV) is related to stress management, emotional well-being, and hypertension. In general, greater HRV correlates with better health. Resonance frequency breathing (RFB), a systematic form of slow breathing, has been used successfully to maximize HRV. Thus, RFB has been used with success in a number of therapeutic settings. However, RFB is currently conducted without musical stimuli. Previous research indicates that musical interventions may achieve results similar to those of using RFB when targeting hypertension, and relaxation effects of music are well-documented. Therefore, including music in RFB interventions could improve the effects of RFB on HRV and relaxation.